Yerusalem Tanah Suci Agama Samawi dalam Perspektif Hukum dan Perdamaian - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2001)
The sincere confessing of Jerussalem as a holy land for three major religions would indicate new paradigm ofpeace issues through redefinement from absolute nationalism into reiative islamic nationalism.